SYSTEMATIZATION AND INSURANCE OF INNOVATIVE RISKS - Sayfullaevich, Sagdiev Ravshanbek (International Journal of Psychosocial Rehabilitation, 2020)
The problems of classification of innovative risks are investigated. The specifics of the activities of insurance companies for insurance of innovative risks as well as features of risks in the field of innovation are considered. Modern approaches to the classification of innovative risks are revealed. The necessity of developing a classification of innovative risks is substantiated. Key problems and prospects for the development of insurance of innovative risks in the domestic economy are identified.